2019
DOI: 10.1186/s12916-018-1233-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety, activity, and molecular heterogeneity following neoadjuvant non-pegylated liposomal doxorubicin, paclitaxel, trastuzumab, and pertuzumab in HER2-positive breast cancer (Opti-HER HEART): an open-label, single-group, multicenter, phase 2 trial

Abstract: BackgroundThe Opti-HER HEART trial aimed to optimize activity while minimizing cardiac risk by combining trastuzumab, pertuzumab, and paclitaxel with non-pegylated liposomal doxorubicin in the treatment of HER2-positive early breast cancer.MethodsPatients with stage II–IIIB HER2-positive breast cancer received neoadjuvant trastuzumab, pertuzumab, paclitaxel, and a non-pegylated liposomal doxorubicin every three weeks for six cycles. The primary endpoint was cardiac safety during neoadjuvant therapy. Type A (sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 55 publications
3
35
0
Order By: Relevance
“…A number of studies reported clinical RRs of 58% to 91% and pCRs of 3% to 41% after NAC in patients with BC. 8 21 , 26 Although there is no consensus concerning the optimal protocol for treating BC, it is generally agreed that anthracyclines and taxanes are among the best options. Phase II and III trials have been conducted to examine different combinations of these agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies reported clinical RRs of 58% to 91% and pCRs of 3% to 41% after NAC in patients with BC. 8 21 , 26 Although there is no consensus concerning the optimal protocol for treating BC, it is generally agreed that anthracyclines and taxanes are among the best options. Phase II and III trials have been conducted to examine different combinations of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Phase II and III trials have been conducted to examine different combinations of these agents. 8 21 , 26 The clinical RR of doxorubicin and docetaxel as NAC for BC was 70%. 10 Regarding the use of the combination of epirubicin, cyclophosphamide, and paclitaxel as NAC for patients with stage II–III BC, the ORR and pCR rate were 83.7 and 15.1% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical value of the HER2-E subtype in HER2+ breast cancer is starting to be elucidated. From a therapeutic perspective, the HER2-E subtype has shown, across 14 clinical trials and ∼2,000 patients, higher sensitivity to anti-HER2-based therapies than the non-HER2-E subtypes [7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, not all HER2-E tumors achieve a complete response following anti-HER2-based therapies.…”
mentioning
confidence: 99%
“…In the combination therapy with multiple anti-HER2-targeting drugs, that is, in the NeoSphere trial [15], compared with trastuzumab plus docetaxel, the new adjuvant trastuzumab plus docetaxel added pertuzumab (a HER2-directed monoclonal antibody) signi cantly increased the proportion of patients who achieved complete pathological remission. For most HER2-positive early breast cancer patients, multidrug chemotherapy and dual HER2 blockade should be considered [16,17]. Giordano et al [18] also suggested the combination of trastuzumab, pertuzumab, and taxanes for rst-line treatment.…”
Section: Introductionmentioning
confidence: 99%